2021
DOI: 10.3390/ijerph18189640
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intensity, Frequency, Duration and Volume of Physical Activity in Children and Adolescents on Skeletal Muscle Fitness: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Physical activity could improve the muscle fitness of youth, but the systematic analysis of physical activity elements and muscle fitness was limited. This systematic review and meta-analysis aim to explore the influence of physical activity elements on muscle fitness in children and adolescents. We analyzed literature in Embase, EBSCO, Web of Science, and PubMed databases from January 2000 to September 2020. Only randomized controlled studies with an active control group, which examined at least 1 muscle fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, this is the first systematic review in patients with PD that attempts at evaluating the effect on BDNF levels of different characteristics of exercise, such as intensity, volume and type. A similar analysis was carried out in previous systematic reviews of the literature in youth and athletes (Lesinski et al, 2016;Wu et al, 2021), but not in patients with PD.…”
Section: Discussionmentioning
confidence: 80%
“…To the best of our knowledge, this is the first systematic review in patients with PD that attempts at evaluating the effect on BDNF levels of different characteristics of exercise, such as intensity, volume and type. A similar analysis was carried out in previous systematic reviews of the literature in youth and athletes (Lesinski et al, 2016;Wu et al, 2021), but not in patients with PD.…”
Section: Discussionmentioning
confidence: 80%
“…The lack of improvements on other muscular fitness components (i.e. abdominal muscular endurance and upper limbs power) may be attributed to the focus on higher aerobic intensity physical activities instead of more resistance-based exercises, agreeing with how the intervention is designed may be a crucial factor for success [ 39 ] since usually muscular fitness improvements are observed within physical activity-based [ 40 ] and school-based [ 41 ] interventions amongst children and adolescents. Moreover, García-Hermoso et al [ 22 ] systematically reviewed the literature and demonstrated that physical education interventions based on quality over quantity may be sufficient to increase health-related physical fitness components because it integrates a conscientiously structured and planned physical education class.…”
Section: Discussionmentioning
confidence: 99%
“…The limit of no more than six hours of sports performance a week was set arbitrarily. Yet, physical activity and the balance between active and sedentary time is an important aspect influencing muscle and skeletal growth (Gabel et al, 2015; Meinhardt et al, 2017; Tan et al, 2018; Wu et al, 2021; Zymbal et al, 2019). No detailed documentation on sport participation or physical activity was collected in the included children.…”
Section: Discussionmentioning
confidence: 99%